Effects of aerobic exercise interventions on cognitive function, sleep quality, and quality of life in older adults with mild cognitive impairment: a systematic review and meta-analysis - Shu, Wanyu; Chen, Liang; Qiu, Jiadong; Kim, Sung Min (Frontiers in Neurology, 2025)
BackgroundAerobic exercise, as a non-pharmacological intervention, has been widely recognized for its potential benefits on cognitive function in individuals with mild cognitive impairment (MCI). However, systematic evidence regarding its effects on other critical health domains, such as sleep quality and quality of life, remains limited. Moreover, previous meta-analyses have typically included a relatively small number of randomized controlled trials (RCTs), which may constrain the generalizability and objectivity of their findings.ObjectiveThis study aimed to evaluate the effects of aerobic exercise on cognitive function, sleep quality, and quality of life in older adults with MCI, and to identify key exercise prescription parameters based on the FITT principle (frequency, intensity, time, and type).ResultsA total of 26 randomized controlled trials involving 2,085 individuals with MCI were included. The meta-analysis revealed that aerobic exercise had a statistically significant positive effect on global cognitive function (SMD = 0.81, 95% CI: 0.58–1.05, p < 0.00001) and quality of life (SMD = 1.26, 95% CI: 0.70–1.82, p < 0.00001). However, no significant improvement was observed in sleep quality (SMD = 0.07, 95% CI: −1.79–1.93, p = 0.94). Subgroup analysis further indicated that interventions conducted four times per week, lasting more than 50 min per session, at moderate intensity, and primarily involving walking were most effective in improving cognitive function.ConclusionThe findings of this study demonstrate that aerobic exercise may significantly improve cognitive function and quality of life in older adults with MCI, with enhanced effects observed when intervention parameters are optimized.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024495979, Unique Identifier: CRD42024495979.